2015
DOI: 10.1681/asn.2014050477
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ADAM17 Level Reflects Disease Activity in Proteinase-3 ANCA-Associated Vasculitis

Abstract: ANCA-associated vasculitides are characterized by inflammatory destruction of small vessels accompanied by enhanced cleavage of membrane-bound proteins. One of the main proteases responsible for ectodomain shedding is disintegrin and metalloproteinase domain-containing protein 17 (ADAM17). Given its potential role in aggravating vascular dysfunction, we examined the role of ADAM17 in active proteinase-3 (PR3)-positive ANCA-associated vasculitis (AAV). ADAM17 concentration was significantly increased in plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…A few studies indicate that miRNAs are involved in the inflammatory response of AAV, which may facilitate the endothelial injury. It was 14 demonstrated that miRNA‐634 was significantly upregulated in the peripheral blood of active AAV patients and induced a pro‐inflammatory phenotype of macrophages. miRNA‐155 was upregulated in the kidney of patients with ANCA‐associated crescentic glomerulonephritis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies indicate that miRNAs are involved in the inflammatory response of AAV, which may facilitate the endothelial injury. It was 14 demonstrated that miRNA‐634 was significantly upregulated in the peripheral blood of active AAV patients and induced a pro‐inflammatory phenotype of macrophages. miRNA‐155 was upregulated in the kidney of patients with ANCA‐associated crescentic glomerulonephritis 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We also observed a weak correlation between Ang2 and ADAM17. Ang2 is released to the plasma from WPBs of activated endothelial cells21, and ADAM17 is co-localized with Ang2 in the WBPs26, which could explain this correlation. However, as ADAM17 plasma levels seem to be elevated as a response to disease in general, whereas Ang2 plasma levels are particularly increased in SM, it seems unlikely that the increase of ADAM17 plasma levels was primarily due to activation of endothelial cells and subsequent release of WPB.…”
Section: Discussionmentioning
confidence: 92%
“…However, the origin of ADAM17 in plasma is unknown. Secretion of enzymatically active ADAM17 on extracellular microparticles has been found in the plasma and associated with disease activity of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis26. ANCA-associated vasculitis, as malaria, features an excessive inflammatory response, which leads to the shedding of adhesion molecules and cytokines, such as TNFα3132.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of ADAM-17 to control and influence other molecules of the immune system is now the subject of extensive investigation. It is now well established that ADAM-17 mediated shedding of cell surface molecules are involved in progression of multiple pathological condition [82,[93][94][95][96]. ADAM-17-induced IL-6 trans-signaling-mediated pathogenesis is now known to be a common feature of inflammatory bowel disease as well as of many respiratory diseases [97][98][99][100][101].…”
Section: Adam-17: Where All Light Tends To Gomentioning
confidence: 99%